The tricornered Ser/Thr protein kinase is regulated by phosphorylation and interacts with furry during Drosophila wing hair development. - He, Y.; Fang, X.; Emoto, K.; Jan, Y.N.; Adler, P.N. (Molecular Biology of the Cell, 2005)
The Trc/Ndr/Sax1/Cbk1 family of ser/thr kinases plays a key role in the morphogenesis of polarized cell structures in flies, worms, and yeast. Tricornered (Trc), the Drosophila nuclear Dbf2-related (Ndr) serine/threonine protein kinase, is required for the normal morphogenesis of epidermal hairs, bristles, laterals, and dendrites. We obtained in vivo evidence that Trc function was regulated by phosphorylation and that mutations in key regulatory sites resulted in dominant negative alleles. We found that wild-type, but not mutant Trc, is found in growing hairs, and we failed to detect Trc in pupal wing nuclei, implying that in this developmental context Trc functions in the cytoplasm. The furry gene and its homologues in yeast and Caenorhabditis elegans have previously been implicated as being essential for the function of the Ndr kinase family. We found that Drosophila furry (Fry) also is found in growing hairs, that its subcellular localization is dependent on Trc function, and that it can be coimmunoprecipitated with Trc. Our data suggest a feedback mechanism involving Trc activity regulates the accumulation of Fry in developing hairs.